Effectiveness and safety of polygeline in patients with hypovolemia due to trauma - Ajai Singh; Sabir Ali; Rohita Shetty (Journal of Emergencies, Trauma and Shock, 2017)
Background: This retrospective study examined the effectiveness and safety of polygeline in adult patients with hypovolemia due to traumatic injury. Materials and Methods: Polygeline was administered after evaluating the amount of blood loss and estimating hematological and biochemical parameters. Changes in vital signs, serum electrolytes, arterial pH, and serum lactate were evaluated. The safety was evaluated by recording the adverse events if any. Results: Sixty patients with the mean age 37.5 ± 11.26 years were included in the study. All patients had blood loss < 20%. The mean total polygeline administered was 1025.0 ± 464.18 ml. Blood transfusion was required in 3.33% of patients. Diastolic, systolic, and mean arterial blood pressure and pulse rate significantly increased after 1 h of polygeline administration (P < 0.0001). There was a trend toward increase in urine output (P = 0.0715) after 1 h. The improvement in vital parameters was consistent at 6, 14, and 18 h after administration of polygeline. Arterial pH significantly increased from 7.2 ± 0.12 to 7.3 ± 0.11 after 1 h of administration (P < 0.0001) and was consistent till 24 h (P = 0.035). Blood lactate decreased after 1 h (P < 0.0001). Changes in laboratory parameters were not clinically significant. After mean duration hospital stay of 10.5 ± 4.63 days all patients were discharged without any clinically significant abnormality or adverse event. Conclusion: Polygeline improved hemodynamic stability in patients with hypovolemia due to traumatic injury. The improvement was seen within 1 h (golden hour) of polygeline administration and maintained consistently. Polygeline can be safely administered to patients with traumatic injury to improve hemodynamic parameters and achieve stability.